Economic preferences and trade outcomes - Alex Korff; Nico Steffen (Review of World Economics, 2021)
Integrating the Global Preference Survey (GPS) and its data of unique scope on national preference structures in patience, risk attitude and reciprocity into a gravity framework, this paper is the first to explore a potential influence on international trade outcomes of economic and social preferences in a unified setting. Adding to the evidence on preferences' importance for aggregate outcomes, the authors find marked differences in trade flows and relationships, both on the country-level and between bilateral partners. Their main results suggest that countries differing in their willingness to behave negatively reciprocal tend to trade significantly less amongst each other due to the destabilizing effect of unexpected punishments. On the other hand, countries that are patient or risk-averse tend to shift towards exporting more differentiated goods as opposed to homogeneous goods and vice versa. We propose term and risk transformation considerations as the driving mechanisms for this relationship.
Keywords: F10; F14; D01; D91; Z10; 330; Trade determinants; Non-tariff barriers; Economic preferences; Sociocultural variation